Reviewing the Insights of Confinement and Social Distancing as Measures Involved in the Prevention of the COVID-19 Pandemic - Georges Pius Kamsu Moyo⃰; Dany Hermann Ngwanou; Daniel Armand Tague Kago; Nelly Kamgaing; Ginette Claude Mireille Kalla; Andreas Chiabi; Paul Olivier Koki Ndombo (Journal La Sociale, 2020)
Confinement and social distancing have been widely used in the prevention of the COVID-19 pandemic, as interventions consisting in reducing physical contact between individuals to prevent the spread of the disease. In order to demonstrate the pattern of these measures, we did a review of pertinent articles on the subject available online. We found that though confinement and social distancing significantly contributed to the mitigation of the COVID-19 infection in a number of countries worldwide, there however exist a dilemma in choosing between the expected benefits and adverse effects, especially when applied on a large scale. Thus considerations with regards to socio-anthropological and politico-economic impacts should be considered in order to protect citizens, especially the vulnerable. Besides, population information, education and communication helps to increase adherence and observation of recommendations. However, further improvements need to be implemented in other to render these measures more bearable and less restrictive while ameliorating their efficacy.